2016
DOI: 10.1007/s10461-016-1495-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HIV and Inconsistent Condom Use Among Female Sex Workers in Ukraine

Abstract: While female sex workers (FSWs) carry one of the highest risks of HIV transmission, little is known about predictors of HIV and risky behavior of FSWs in Ukraine. In this study of 4806 Ukrainian FSWs, the prevalence of HIV was 5.6 %. FSWs had higher odds to be HIV infected if they had lower income, were older, injected drugs, experienced violence, and solicited clients on highways. Inconsistent condom use with clients was reported by 34.5 % of FSWs. FSWs who solicited clients at railway stations, via media, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…It is inferred that female sex workers who have a permanent partner present higher motivation to protect themselves and, thus, also protect their partners. Regarding the use of alcoholic drinks, studies performed in Ukraine and Uganda corroborate the findings in this research ( 9 , 23 ) .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is inferred that female sex workers who have a permanent partner present higher motivation to protect themselves and, thus, also protect their partners. Regarding the use of alcoholic drinks, studies performed in Ukraine and Uganda corroborate the findings in this research ( 9 , 23 ) .…”
Section: Discussionsupporting
confidence: 87%
“…Besides, other international studies have reported higher rates: 34.5% in Ukraine, and 76.8% in Uganda ( 9 , 23 ) . The inconsistent condom use among women acting on sexual work is a concerning data.…”
Section: Discussionmentioning
confidence: 87%
“…20 Iakunchykova & Burlaka, 2020, in a study of female sex workers in Ukraine, reported that nonpermanent condom use was associated with variables such as lower age, alcohol consumption, having fewer customers, and lack of participation in HIV prevention programs. 21 In a study done by Bandyopadhyay et al among 296 female sex workers in India, 37.5% did not use condoms continuously. Having a non-monetary partner, violence, and alcohol-related sex were reasons for not using condoms consistently.…”
Section: Introductionmentioning
confidence: 97%
“…The target sample size for each round of surveys is 560 FSWs and 370 clients based on 80% power and a 5% alpha error in two outcomes: experience of physical violence among FSW during encounters with clients (current level 42%) [32, 35] and injecting drug use among clients (current level 26%) [45]. This will also account for a 10% ineligibility, observed in our previous work in Dnipro.…”
Section: Methodsmentioning
confidence: 99%
“….In Ukraine, there are an estimated 80,100 female sex workers (FSWs) with an HIV prevalence of 5.2% in 2016 [11, 14, 32]. Very little data exist on whether sex work changes during times of conflict.…”
Section: Introductionmentioning
confidence: 99%